Mensuração da influência de qualidade, valor, satisfação e envolvimento do consumidor sobre intenções comportamentais em restaurantes finos da cidade de São Paulo - Peters Filho, Theodoro Agostinho (2003)
This study intends to cover the inter-relation amongst perceived quality, consumer value, and satisfaction from marketing point of view, considered the involvement of consumers in terms of subject, object and situation, and its effects upon behavior intentions in the scenario of fine restaurants in the city of Sao Paulo - Brazil. Starting with state of the art review about these constructs in the marketing scope, added by personal in depth interviews with fine restaurant managers and users, it is made a quantitative research with consumers aiming the comparative test of five nested models extracted from marketing theory, and the connected hypotheses of these constructs inter-relation and consumer involvement influence in the process. At the end, there are the research sintesis, comments, and suggestions for additional studies in the area.